2010
DOI: 10.1063/1.3326074
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an imposed flow on the stability of a gravity current in a near horizontal duct

Abstract: We study experimentally the effect of a mean flow imposed on a buoyant exchange flow of two miscible fluids of equal viscosity in a long tube oriented close to horizontal. We measure the evolution of the front velocity Vf as a function of the imposed velocity V0. At low V0, an exchange-flow dominated regime is found, as expected, and is characterized here by Kelvin–Helmholtz-like instabilities. With increasing V0 we observed that the flow becomes stable. Here also Vf increases linearly with V0 with slope of &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 16 publications
1
62
0
Order By: Relevance
“…The novelty of our work with respect to Seon et al (2004Seon et al ( , 2005Seon et al ( , 2006Seon et al ( , 2007a is the study of imposed displacement velocities,V 0 > 0. Preliminary results of our study were reported in Taghavi et al (2010). As an increasingly strong mean flow,V 0 > 0, was imposed on a pipe exchange flow the observations suggested a primary classification in terms of 3 regimes.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…The novelty of our work with respect to Seon et al (2004Seon et al ( , 2005Seon et al ( , 2006Seon et al ( , 2007a is the study of imposed displacement velocities,V 0 > 0. Preliminary results of our study were reported in Taghavi et al (2010). As an increasingly strong mean flow,V 0 > 0, was imposed on a pipe exchange flow the observations suggested a primary classification in terms of 3 regimes.…”
Section: Introductionmentioning
confidence: 87%
“…injecting inertia reduces instability. Taghavi et al (2011) studied the flows that occur at the transition between regimes p1 & p2. Right at the transition we find flows for which the less dense displaced fluid remains in a stationary layer at the top of the pipe, over the relatively long duration of our experiments, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mixing rates were also shown to increase with increasing inclination angles when the displaced fluid is also the denser one. Recently, Taghavi et al 33,34 studied the effects of imposed mean flow on a buoyant exchange flow of two miscible fluids in a near horizontal pipe/channel. For very low imposed velocity, they observed an inertial gravity current and KH-like instabilities in the interfacial region separating the fluids.…”
Section: Introductionmentioning
confidence: 99%